Новое издание трактата Аристотеля об афинской политии - Бузескул, В.П.; Buzeskul, V.P. (Х. : Типография Адольфа Дарре, 1893)
Владислав Петрович Бузескул (1858–1931) — историк-античник, историограф, академик АН СССР (1922), академик НАНУ (1925). Занимал должности приват-доцента и профессора Харьковского университета (1885—1924). Научно-литературная деятельность Бузескула весьма разнообразна, но главные труды его относятся к области древнегреческой истории. Несколько его работ посвящены истории Харьковского университета. Buzeskul Vladislav Petrovich (1858-1931), historian, historian, academician of the Academy of Sciences of the USSR (1922), Academician of the National Academy of Sciences (1925). He held the positions of assistant professor and professor of Kharkov University (1885-1924). Buzeskul ’s Scientific and literary activities are very diverse, but his main works are in the area of ancient Greek history. Several of his works are devoted to the history of the Kharkov University.
Keywords: трактат Аристотеля; афинская полития